Mathematical Communication of Vocational High School Students in Solving Papuan Ethnomathematics-Based Problems - Dewi Kristika Findia Ning Tyas; Marthinus Y. Ruamba; Ririn Dwi Agustin; Pujilestari Pujilestari (Universitas Pendidikan Mandalika, 2026)
This study examines how Indonesian vocational high school (SMK) students communicate mathematically while solving systems of three-variable linear equations (SPLTV) embedded in Papuan ethnomathematical contexts. Using a qualitative descriptive design, the study involved ten Grade 10 students representing ten vocational departments. Data were collected through students’ written solutions to ethnomathematics-based SPLTV tasks (e.g., contexts involving culturally familiar objects such as noken and local economic practices) and follow-up semi-structured interviews intended to clarify students’ reasoning, procedural choices, and interpretation of results. Analysis employed a rubric-guided coding scheme comprising three observable indicators of mathematical communication: (1) mathematical expression/modeling (translating contextual information into variables and SPLTV equations), (2) identifying relevant information and coherently explaining solution procedures, and (3) drawing contextual conclusions that interpret solutions in relation to the problem situation. To ensure consistent reporting, each indicator was evaluated by evidence source written work (W), interview evidence (I), or both (W+I) allowing the study to distinguish between students who understood an element but did not document it in writing. Findings indicate that all participants were able to construct an SPLTV model from the cultural context, and most were able to explain elimination–substitution procedures, although several omitted key communication components (e.g., “given/asked” statements or an explicit concluding sentence) in their written work. Overall, eight of ten students produced a valid contextual conclusion when evidence from written work and/or interviews was considered, whereas two students struggled with core procedural steps and therefore could not reach a meaningful conclusion. These results suggest that Papuan cultural contexts can support meaning-making and initial modeling, but explicit support for procedural fluency and written communication norms remains necessary to produce complete, accountable solutions.